2018
DOI: 10.1002/jper.17-0403
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose powder for subgingival air‐polishing during periodontal maintenance therapy: A randomized controlled trial

Abstract: Background Air‐polishing appears to be a promising procedure for subgingival biofilm removal in periodontal treatment. The aim of this study was to compare trehalose powder for subgingival air‐polishing with sonic debridement in residual periodontal pockets during maintenance therapy. Methods In this blinded, randomized, controlled clinical trial conducted over 6 months with a split‐mouth design, single‐rooted teeth in 44 participants with residual pocket depths of 5 mm and bleeding or >5 mm with and without b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…Within the last decade, more powders such as trehalose have been established. Mechanical efficiency of both glycine and trehalose powders has been shown in detail [10,17]. Surprisingly, data regarding the effect of these powders on periodontal cells are scarce, although these powders get into direct contact with the respective cells.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, more powders such as trehalose have been established. Mechanical efficiency of both glycine and trehalose powders has been shown in detail [10,17]. Surprisingly, data regarding the effect of these powders on periodontal cells are scarce, although these powders get into direct contact with the respective cells.…”
Section: Introductionmentioning
confidence: 99%
“…This is why most studies have strongly emphasized the view of APDs as an adjuvant treatment method following the removal of mineralized bacterial deposits using conventional subgingival debridement [ 26 ]. This is the main reason why there has been a search for new low-abrasion powders for subgingival application that are equally effective [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients perceive the use of hand instruments or ultrasonic scalers for subgingival debridement as unpleasant, while the use of air-polishing devices is often reported to be more comfortable and less painful [ 25 , 33 ]. A systematic review of patients’ perception of the use of air-polishing devices during periodontal treatment by Bühler et al reported that discomfort was consistently equivalent or lower when air-polishing powders consisting of glycine or erythritol were applied in comparison to root surface instrumentation using hand instruments or ultrasonic devices [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations